A prospective observational study to analyse clinical profile of varicose vein cases treated in a tertiary care hospital - Mani, Maragadha; A., Anand (International Surgery Journal, 2019)
Background: Varicose veins are common vascular disorder. The study was conducted to analyse the clinical presentation, treatment options and complications of varicose veins. Methods: This observational study was conducted in Thanjavur Medical College Hospital. Adults with clinically diagnosed unilateral or bilateral varicose veins of lower limbs were studied in surgical wards between August 2013 to July 2014. The demographic data and presenting symptoms, signs and previous treatment were collected using a structured proforma. Thorough clinical examination, duplex scan and abdominal and pelvic examination were done in all cases to find out the secondary causes. Peripheral vascular system was examined. All the patients were followed regularly for the period of one month to one year after treatment. Results: A total of 60 cases were included. Most participants belonged to 2nd and 3rd decade of life. 55 (91%) participants were male and5 (9%) participants were females. 45 (75%) participants were agriculturists. 10 (17%) participants had bilateral involvement. Most participants 30 (50%) participants had 1 to 5 years duration of disease, most common clinical presentation of the study participants was varicosity with 70.0%, followed by lipodermo sclerosis, leg pain, hyperpigmentation, pruritus as 63.0%, 56.0%, 15% and 11.6% respectively. 17 (28.33%) patients were present with a venous ulcer. 32 (53%) participants were managed surgically, and 28 (47%) participants were managed conservatively. Most participants were treated with multiple ligation 21.8% followed by trendelenburg operation+ stripping18.75%. Conclusions: Regarding the treatment, surgery is the treatment of choice for primary varicose veins and conservative treatment for secondary varicose veins.